The Mathematics Teacher Education Partnership : the power of a networked improvement community to transform secondary mathematics teacher preparation - Martin, W. Gary; Lawler, Brian (Educator); Lischka, Alyson E.; Smith, Wendy Marie, 1975- (AMTE professional book series ;, 2019)
"This book provides an overview of a body of work conducted over the past seven years related to the preparation of secondary mathematics teachers by the Mathematics Teacher Education Partnership (MTE-Partnership), a national consortium of more than 90 universities and 100 school systems. The MTE-Partnership is organized as a Networked Improvement Community (NIC), which combines the disciplined inquiry of improvement science with the power of networking to accelerate improvement by engaging a broad set of participants. The MTE-Partnership is addressing key challenges in secondary mathematics teacher preparation, including: Supporting the development of content knowledge relevant to teaching secondary mathematics; Providing effective clinical experiences to teacher candidates; Recruiting secondary mathematics teacher candidates, ensuring program completion and their subsequent retention in the field as early career teachers; Supporting overall transformation of secondary mathematics teacher preparation in alignment with these challenges; and Ensuring a focus on equity and social justice in secondary mathematics teacher recruitment, preparation, and induction. This book outlines existing knowledge related to each of these key challenges, as well as the work of Research Action Clusters (RACs) formed to address the challenges. Each RAC includes participants from multiple institutions who work collaboratively to iteratively develop, test, and refine processes and products that can help programs more effectively prepare secondary mathematics teacher candidates. The book describes promising approaches to improving aspects of secondary mathematics teacher preparation developed by the RACs, including specific products that have been developed, which will inform the work of others involved in secondary mathematics teacher preparation. In addition, reflections on the use of the NIC model provides insights for others considering this research design. Particular references to the Standards for Preparing Teachers of Mathematics (Association of Mathematics Teacher Educators, 2017) are included throughout the book"--